Scene-Context-Aware Indoor Object Selection and Movement in VR - Wang, Miao; Ye, Zi-Ming; Shi, Jin-Chuan; Yang, Yang-Liang (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2021)
Virtual reality (VR) applications such as interior design typically require accurate and efficient selection and movement of indoor objects. In this paper, we present an indoor object selection and movement approach by taking into account scene contexts such as object semantics and interrelations. This provides more intelligence and guidance to the interaction, and greatly enhances user experience. We evaluate our proposals by comparing them with traditional approaches in different interaction modes based on controller, head pose, and eye gaze. Extensive user studies on a variety of selection and movement tasks are conducted to validate the advantages of our approach. We demonstrate our findings via a furniture arrangement application.